1994
DOI: 10.1073/pnas.91.11.4994
|View full text |Cite
|
Sign up to set email alerts
|

The gene for the neuropeptide gonadotropin-releasing hormone is expressed in the mammary gland of lactating rats.

Abstract: The high concentration of gonadotropinreleasing hormone (GnRH) In milk of several species implies that the mammary and is either a site of synthesis for this neuropeptide or that it is efficiently concentrated from plasma by this organ. By PCR amplification ofmammary gland cDNA, we have demonstrated expression of the mRNA for GnRH. The GnRH mRNA was present In the mammargland of pregnant and lactating rats but not of virgin rats, implying that expression ofthe GnRH gene is activated during pregnancy probably b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Among these, variation in the expression of GnRH in mammary tissues has been reported [9,18]. In the present study, we examined the variation of annexin A5 expression in mammary tissues.…”
mentioning
confidence: 99%
“…Among these, variation in the expression of GnRH in mammary tissues has been reported [9,18]. In the present study, we examined the variation of annexin A5 expression in mammary tissues.…”
mentioning
confidence: 99%
“…1A) and confirmed that the fragments that were amplified originated from RNA. Unlike the transcript for GnRH that was evident in mammary glands of pregnant and lactating but not of virgin rats [6], the transcript for the GnRH receptor was present in the mammary glands of all animal models that were examined including the virgin rat. The mRNA for the GnRH receptor has also been detected in the breast of human [ 191 but not in that of mouse [20], suggesting a species-specific regulation for this gene.…”
Section: Discussionmentioning
confidence: 89%
“…A considerable amount of GnRH is synthesized by the breast [6]. GnRH produced by the mammary gland may act locally in a paracrine and/or an autocrine way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations